The Influence of Information Technology Utilization, the Principle of Consistency, and Internal Control on the Efficiency of Accounting Reporting for Zakat, Infaq/Alms (PSAK 109) in Zakat Management Organizations in West Sumatra - Zora, Fera (The Future of Education Journal, 2025)
The purpose of this study is to investigate how internal control, consistency principles, and information technology utilization affect zakat and infaq/clms accounting reporting. The effectiveness of a sample of 30 OPZ in West Sumatra is the main subject of this descriptive quantitative study. A survey questionnaire given to OPZ's financial management was used to gather data for this study. The data was analyzed using multiple regression analysis. The findings indicate that: 1. The efficiency of accounting reporting for zakat, infaq, and alms is greatly enhanced by the use of information technology (PSAK 109). 2) The efficiency of accounting reporting for zakat, infaq, and charity is greatly enhanced by the consistency principle (PSAK 109). 3) Internal Control has significant positive influence on the effectiveness of accounting reporting of zakat, infaq/alms (PSAK 109).